Rapid co-deposition of graphene oxide incorporated metal-phenolic network/piperazine followed by crosslinking for high flux nanofiltration membranes - Yang, Yang (2021)
In this study, we presented a novel nanofiltration membrane fabrication strategy through rapid co-deposition of a versatile platform – metal phenolic networks (MPNs) and piperazine (PIP) on a porous substrate followed by trimesoyl chloride (TMC) crosslinking. Inspired by the catechol chemistry, tannic acid (TA) was functionalized to tether PIP monomers, and participated in the co-deposition via coordination bonds with Fe3+ ions on a substrate to form Fe3+/TA-PIP complex. A series of analyses (SEM, XPS, FT-IR, water contact angle and zeta potential) confirmed the successful synthesis Fe3+/TA-PIP deposition and polyamide (PA) layer. The resultant membrane exhibited water permeability of 13.73 LMH/bar and 89.52 % for MgSO4 rejection. The fabrication was further improved by embedding modified graphene oxide (GO) nanosheets into the Fe3+/TA-PIP complex. The optimized nanocomposite membrane achieved a water permeability at 21.66 LMH/bar, along with a well maintained MgSO4 rejection at 91.25 % and NaCl/MgSO4 selectivity (α) at 10.02 under 2 bar operation pressure. The rapid co-deposition mediated by nanomaterials incorporation provides an effective approach to design high performance thin film composite (TFC) membrane.